PEMANFAATAN METODE ACTIVITY BASED COSTING DALAM SISTEM INFORMASI AKUNTANSI PENENTUAN BIAYA PADA BENGKEL MUJI JAYA - Sukemi Kamto Sudibyo; Fitri Puji Astuti (LPPM Politeknik Pratama, 2021)
The Muji Jaya Workshop in determining the cost of body repair, it still uses a manual estimate model with paper media which will result in losses if the calculation of the cost of body repair that is informed to the customer is not enough so that the body repair costs received are not sufficient for the needs of raw material costs and labor costs in body work. The repair and preparation of financial statements will be disrupted and delayed for a long time if the note paper used is lost or damaged. This results in the owner not being able to make decisions quickly, precisely and accurately. From these various problems, Workshop Muji Jaya implements the use of the activity based costing method in the accounting information system for determining body repair costs in order to make it easier to determine the cost of body repairs to be more accurate and in presenting financial statements to be easier and more efficient because this method is guided by the assignment of costs to products. or services based on all required activities. Keywords: estimation, cost, activity based costing